Mortality and morbidity in surgically treated patients with petroclival meningiomas: a systematic review and meta-analysis of case series. (4th July 2022) - Barić, Hrvoje; Trkulja, Vladimir; Peterković, Vjerislav; Mrak, Goran
Abstract: Background: Reports on petroclival meningioma (PCM) surgical mortality and morbidity often deviate from established standards; as such, a comprehensive summary is lacking. Methods: Eligibility/sources . Peer-reviewed case series of at least 10 PCM patients identified from PubMed, Web of Science, Ovid, or Google Scholar. Outcomes . Primary: mortality, tumor recurrence, any cranial nerve deficit (CND); other: individual CNDs, other complications. Data synthesis . Random-effects meta-analysis/meta-regression [effects: surgical approach (supratentorial, S; infratentorial, I; combined, (C), average age and follow-up, sample size, and percent of patients with gross-total resection (GTR)] of logit-transformed proportions. Results: Data . 73 case-series/3553 patients. Mortality . Adjusted predicted mortalities of 2.4%, 2.5%, and 1.2% (50-month follow-up) for the S, I, and C approaches, respectively, with the upper limits of the 95% credibility intervals at 3.3%, 3.7%, and 3.6%, respectively. Recurrence . Adjusted predicted recurrences of 5.5%, 11.1%, and 12.0% (50-month follow-up and 57% GTR) for the S, I, and C approaches, respectively; recurrence was positively associated with follow-up period and negatively associated with having received GTR. At all covariates at median values but at GTR 90% predictions: 3.1% (95%CI 3.1–9.8), 6.3% (3.8–10.4), and 6.9% (3.4–13.2) with the S, I, and C; prediction credibility intervals 1–4% and 22.4%. Any CND . Adjusted predicted probabilities of 37.2%, 23.4%, and 29.5% (at median covariate values) for the S, I, and C approaches, respectively; prediction credibility intervals ranged from <10% to 78%. Other outcomes . The most common individual CNDs were nVII (14.4%), nV (11.5%), and nIII (10.2%); other common complications included motor deficit (10.8%), infection (9.8%), and CSF leak (7.5%). Conclusion: This is the first systematic review on PCM surgical mortality, recurrence, and morbidity. Outcomes differ between surgical approaches and reporting quality varies greatly.